Macroeconomic impacts of climate change mitigation in Latin America: A cross-model comparison - Kober, Tom; Summerton P; Pollitt H; Chewpreecha, U.; Ren X; Wills W; Octaviano C; McFarland J; Beach, Robert H.; Caig Y; Calderón, S.; Fisher-Vanden, Karen; et al. (Elsevier, 2016)
In this paper we analyse macroeconomic consequences of greenhouse gas emission mitigation in Latin America up to 2050 through a multi-model comparison approach undertaken in the context of the CLIMACAP–LAMP research project. We compare two carbon tax scenarios with a business-as-usual scenario of anticipated future energy demand. In the short term, with carbon prices reaching around $15/tCO2 by 2030, most models agree that the reduction in consumer spending, as a proxy for welfare, is limited to about 0.3%. By 2050, at carbon prices of $165/tCO2, there is much more divergence in the estimated impact on consumer spending as well as GDP across models and regions, which reflects uncertainties about technology costs and substitution opportunities between technologies. We observe that the consequences of increasingly higher carbon prices, in terms of reduced consumer spending and GDP, tend to be fairly linear with the carbon price in our CGE models. However, the consequences are divergent and nonlinear in our econometric model, that is linked to an energy system model that simulates step-changes in technology substitution. The results of one model show that climate policy measures can have positive effects on consumer spending and GDP, which results from an investment stimulus and the redistribution of carbon price revenues to consumers.